The Impact of Security, Convenience, and Digital Promotion on Gen Z’s Islamic Banking Interest - Muhammad Irsyam Fi Qolbi; Maryam Bte Badrul Munir (Research of Finance and Banking, 2026)
This study aims to analyze the influence of security, convenience, and digital promotion on Gen Z's interest in becoming customers of Bank Syariah Indonesia (BSI). The rapid development of digital banking has intensified competition among financial institutions, making digital service quality and effective marketing strategies essential for attracting young customers. Previous studies have mainly examined security, convenience, and digital promotion separately or have focused on existing users. This study addresses this gap by integrating these three factors to explain Generation Z's interest in becoming BSI customers. The study employed a quantitative associative approach. The population consisted of Gen Z in Surabaya who had not yet used BSI services. Using purposive sampling, data were collected from 168 respondents through an online questionnaire and analyzed using multiple linear regression. The results show that security, convenience, and digital promotion have a positive and significant influence on Gen Z's interest in becoming BSI customers. Security is the strongest factor in building trust, while convenience improves application usability. Digital promotion also increases Gen Z's interest and awareness of Islamic banking services. These findings provide strategic insights to help BSI improve its digital services and marketing strategies for Generation Z.